ChemInform Abstract: Nuclear and Magnetic Supercells in the Multiferroic Candidate: Pb3TeMn3P2O14. Issue 9 (March 2015) - Silverstein, Harlyn J.; Huq, Ashfia; Lee, Minseong; Choi, Eun Sang; Zhou, Haidong; Wiebe, Christopher R.
Abstract The crystal and magnetic structures of the title compound are determined by synchrotron X‐ray and neutron diffraction.